Pengaruh Budaya Kerja, Gaya Kepemimpinan dan Motivasi Guru terhadap Kinerja Guru SDN pada Gugus II Kecamatan Pangkalan Kuras Kabupaten Pelalawan Riau - Emniswati Emniswati; Sudarno; Jaka Warsihna (Lembaga Anotero Scientific Pekanbaru, 2023)
This study aims to examine the effect of work culture, leadership style and teacher motivation on teacher performance at SDN in Cluster II, Pangkalan Kuras District, Pelalawan Regency, Riau. This study uses multiple linear regression analysis. The sample in this study were 42 teachers. The results of the study show that work culture, leadership style, and teacher motivation simultaneously influence teacher performance. The results of the study also show that partially each variable also influences teacher performance. Recommendations that can be given are the need to maintain and increase returns by maximizing the quantity of employee work such as giving promotions to employees who have good quality work.